ANALISIS PENGARUH JUMLAH PENDUDUK, JUMLAH INDUSTRI DAN PDRB TERHADAP PENERIMAAN PAJAK REKLAME - Aris Maulana; Cut Zakia Rizki; Cut Risya Varlitya; Miksalmina Miksalmina (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to determine the effect of population, the number of industries and the GDRP of advertisement tax receipts in Banda Aceh, Lhokseumawe, Padang and Tanjung Balai. The samples in this study were advertisement tax receipts, population, number of industries and GDRP in Banda Aceh City, Lhokseumawe, Padang and Tanjung Balai for 11 years. From 2007-2017. The data used is secondary data obtained from official documents issued by the relevant agencies. The analytical method used in this study is panel data regression analysis. Regression analysis results show that based on panel data estimation results, it is found empirical evidence that the population has a positive and significant effect on advertisement tax revenue, GDRP also has a positive and significant effect on advertisement tax revenue while the number of industries has a positive but not significant effect on advertisement tax in the City Banda Aceh, Lhokseumawe, Padang and Tanjung Balai.Keywords: advertisement tax, population, number of industries, GDRP.